227k views
1 vote
9/8m - 1/6m = -4 - 11/3

User AlixB
by
6.0k points

1 Answer

4 votes

Answer:

m=-8

Explanation:

im assuming the equation is:
(9)/(8) m-(1)/(6) m=-4-(11)/(3)

find common denominators i choose 24

9/8 = 27/24

1/6 = 4/24

11/3 = 88/24

4 = 96/24

now start solving:

(Note that because denominators are the same you can just ignore them and focus on the numerator)

simplify (27/24)m - (4/24)m to (23/24)m

simplify -(96/24) - (88/24) to -184/24

now you are left with 23/24 m = -184/24

get rid of denominators 23m=-184

Divide -184 by 23 to get m= -8

User Cato
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.